2011
DOI: 10.3354/dao02354
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in cultured channel catfish Ictalurus punctatus spontaneously infected with Streptococcus iniae

Abstract: ABSTRACT:The pathological changes present in channel catfish Ictalurus punctatus spontaneously infected by Streptococcus iniae are described. The most consistent gross findings were marked petechial hemorrhages of the skin and congestion of internal organs, particularly the liver, spleen and kidneys. Other features included color fading at the edge of fin rays, enteritis and ascites. Histological examination showed oedema, degeneration and necrotic changes in many organs. Further, hepatitis, splenitis, interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Because previous studies reported that lesions of ventral skin region are common in various pathogen infections in catfish 31 33 , we used the ventral skin model to determine if it could be used as an infection model. We inoculated AH into the apical side of the ventral skin model for 6 h and investigated tissue integrity and the barrier function compared to no bacteria control.…”
Section: Resultsmentioning
confidence: 99%
“…Because previous studies reported that lesions of ventral skin region are common in various pathogen infections in catfish 31 33 , we used the ventral skin model to determine if it could be used as an infection model. We inoculated AH into the apical side of the ventral skin model for 6 h and investigated tissue integrity and the barrier function compared to no bacteria control.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, in Lates calcarifer, bath exposure of S. iniae could resulted in higher level of mortality within the first 48 h, which is much more significant than oral exposure [42]. In addition, the pathogenic characteristic of S. iniae infection was marked petechial hemorrhages of the skin [43].…”
Section: Expression Profiles Of Chitinase Genes Following Bacterial Cmentioning
confidence: 99%
“…Streptococcus iniae has been reported as one of the most important pathogenic bacteria in aquaculture resulting in severe economic losses of hundreds of millions of dollars annually [ 1 ]. S. iniae is the main causative agent of streptococcosis in wild and farmed fish worldwide, affecting at least 27 different species, including rainbow trout ( Oncorhynchus mykiss ) [ 2 , 3 , 4 ], Nile tilapia ( Oreochromis niloticus ) [ 5 , 6 ] and its hybrids [ 7 ], Siberian sturgeon ( Acipenser baerii ) [ 8 , 9 ], channel catfish ( Ictalurus punctatus ) [ 10 ], barramundi ( Lates calcarifer ) [ 11 , 12 ], red drum ( Sciaenops ocellatus ) [ 13 ] and Japanese flounder ( Paralichthys olivaceus ) [ 14 , 15 ]. Moreover, S. iniae represents a zoonotic risk, usually associated with the handling and preparation of infected fish for consumption [ 16 ].…”
Section: Introductionmentioning
confidence: 99%